2017
DOI: 10.1093/nar/gkx787
|View full text |Cite
|
Sign up to set email alerts
|

Individual-specific edge-network analysis for disease prediction

Abstract: Predicting pre-disease state or tipping point just before irreversible deterioration of health is a difficult task. Edge-network analysis (ENA) with dynamic network biomarker (DNB) theory opens a new way to study this problem by exploring rich dynamical and high-dimensional information of omics data. Although theoretically ENA has the ability to identify the pre-disease state during the disease progression, it requires multiple samples for such prediction on each individual, which are generally not available i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 43 publications
1
47
0
1
Order By: Relevance
“…Changes in ambulation and activities of daily living (ADL) have been used to predict the last 3 years of life . Other examples include attempts to identify indicators through functional analysis and descriptions of pathways that predict a disease state and using omics data to identify pre‐disease states and predict disease progression . Exactly four distress symptoms were found that were clinically and statistically significant for predicting the point of crisis for caregivers of people with dementia…”
Section: Resultsmentioning
confidence: 99%
“…Changes in ambulation and activities of daily living (ADL) have been used to predict the last 3 years of life . Other examples include attempts to identify indicators through functional analysis and descriptions of pathways that predict a disease state and using omics data to identify pre‐disease states and predict disease progression . Exactly four distress symptoms were found that were clinically and statistically significant for predicting the point of crisis for caregivers of people with dementia…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression signatures, easily measured from a tissue sample using high-throughput assays, have been used as a means of stratifying breast cancer samples. This has resulted in computational methods that identify personalized "driver mutation" genes [19], differentially expressed genes and pathways [34], and individualized gene networks [35]. Although genes have been used successfully as biomarkers for cancer prediction tasks [18], it is not clear that gene biomarkers are the most appropriate substrate for classification.…”
Section: Introductionmentioning
confidence: 99%
“…但是, 这两个基于基因组学的进化生物学 研究新方向或学科还没有能准确反映宏观进化和微观 进化的整合, 没有精准瞄准多姿多彩生物性状(phenotype)演化的遗传进化基础(genotype)这一核心问题. 有 鉴于此, 我们在2014年提出了进化系统生物学(evolutionary genotype-phenotype systems biology, eGPS)的 新方向, 并得到了中国科学院"战略性先导专项"- [14,15] , 找出关键的遗传调控基因标记和通路 [16] , 通过 1 反刍动物的进化 反刍亚目是大型陆地哺乳动物中最成功、最大的 一类, 分为6个科: 鼷鹿科(Tragulidae)、长颈鹿科(Giraffidae)、叉角羚科(Antilocapridae)、麝科(Moschidae)、鹿科(Cervidae)和牛科(Bovidae) [28,29] . 反刍动物 物种丰富, 包含了超过200种现存的物种 [30] , 其中牛科 的物种最为丰富, 有140多种 [31,32] ; 而且地理分布非常 广泛, 分布于不同的纬度范围(从热带到北极寒带)、 不同的海拔地区(从平原到高原)、不同的生态环境(从 沙漠到雨林).…”
unclassified